Implementasi Metode Profile Matching untuk Seleksi Penerimaan Anggota Asisten Praktikum (Studi Kasus : Laboratorium Pembelajaran Kelompok Praktikum Basis Data FILKOM) - Fran's Dwi Saputra Atmanagara; Rekyan Regasari Mardi Putri; Sutrisno Sutrisno (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Practicum is a learning method that is attempted to learners to better understand about the related learning materials. With practicum activities are expected learners can be more exploration about the material being studied. One of the factors so that learners can follow practicum activities well is with the guidance of a practicum assistant who has human resources (HR) quality. The selection process at the time of admission of a practicum assistant member is needed to find qualified human resources assistant assistant. The acceptance of a practicum assistant member is not expected to be subjective so that the quality of the assistant laboratory assistant obtained can be in line with expectations, so that no one will be harmed and more easily perform the task as a member of the practicum assistant. Profile Matching is one of the most suitable decision-making methods for selecting membership acceptance according to the required criteria. Profile Matching is a decision-making mechanism by assuming that there is an ideal predictor variable level that must be owned by an individual, not a minimum level that must be met or skipped. The result of system accuracy calculation by implementation Profile Matching method shows an accuracy of 86.6% in the recruitment stages of new members and 83.3% in the division placement stages. The performance of a designed system can be used to make a member accept decision with output in the form of ranking based on the highest end value to the lowest final value.